Experimental study of local scour around T-shaped spur dike in a meandering channel - Tripathi R.P.; Pandey K.K. (My University, 2025)
A spur dike is mainly constructed as a river-training structure and is primarily used to prevent bank erosion. The restriction to flow caused by the construction of a spur dike promotes local scour around the structure. In the case of a dike placed in a channel bend, the scour becomes more aggressive. The literature review found that the research work related to local scour around a spur dike located in a meandering channel is very limited or minimal. Therefore, an experimental investigation was conducted to study the local scour process around a T-shaped spur dike placed at different locations along the outer bank (or concave) of a reverse-meandering channel. Nondimensionalized empirical equations for temporal and maximum local scour depth were developed as the function of the Froude number of approach flow and spur dike location. It is observed that local scour around the dike increases with the increase in Froude number and location in the meander (measured from the entry to meander). The formulation for the maximum scour depth was further evaluated with the experimental data related to the 180o bend, from literature, and it was found that the proposed equation’s application is very much limited. © 2021 The Authors Water Supply.